(untitled) (Orfeu, 2022)
This article consists of excerpts from completed research whose subject was “Life Stories of Music Teachers from the Escolas Parque de Brasília/DF”. This research aimed to understand how the bonds between teachers and the primary school are built and its ramifications are the emphasis on how the experiences of these teachers contribute to their bonding with the school, and the understanding, through (auto)biographical narratives, of how these teachers became the subjects of the experience. The theoretical-methodological approach applied throughout the article is the (auto)biographical research and the source is the (auto)biographical narrative interview. The results reveal that the bonding was started by the teachers themselves in their narratives, understanding that the subject builds and rebuilds new meanings to himself starting from the (auto)biographical movement, going deep in their own life stories with what emerges from their relationship with the school. From these connections a formative device is created to the subject – the bond.